2002
DOI: 10.1081/amp-120014240
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reactive Plasma Processing for Transforming Surfaces of Metals and Intermetallics to Ceramics

Abstract: The surface of Ti, Zr, and TiAl was directly transformed to ceramics with a graded composition by carburizing, nitriding, and oxidizing using novel reactive plasma processing that has been developed by the present authors. Thick modified layers which consist of TiC, TiN, ZrC, ZrN (Zr 2 N), ZrO 2 , and Ti 2 AlN were successfully synthesized by this plasma process. The ceramic layers exhibited higher hardness and elastic modulus than the substrates. The formation behavior of these ceramic layers was analyzed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Depositions were performed under 1.33× 10 4 to 1.33 × 10 6 Pa in CH 4 atmosphere. Inoue et al [6] investigated the surface of Ti, Zr and TiAl that was directly transformed to ceramics with a graded composition by carburizing, nitriding and oxidizing using novel reactive plasma processing. They found that the interstitial C atoms exhibit high covalency with the proximal Zr atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depositions were performed under 1.33× 10 4 to 1.33 × 10 6 Pa in CH 4 atmosphere. Inoue et al [6] investigated the surface of Ti, Zr and TiAl that was directly transformed to ceramics with a graded composition by carburizing, nitriding and oxidizing using novel reactive plasma processing. They found that the interstitial C atoms exhibit high covalency with the proximal Zr atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ZrC films have been prepared by vacuum evaporation [8], reactive magnetron sputtering deposition [9], chemical vapor deposition [10], reactive plasma processing [6] and vacuum plasma spray processes [11]. However, all these ZrC films were synthesized at higher substrate temperatures approximately N380°C.…”
Section: Introductionmentioning
confidence: 99%
“…7) [38]. Inoue et al recently reported the plasma nitridation of TiAl to form Ti 2 AlN, and by quantum chemical simulation found evidence that formation of the ternary nitride was influenced primarily by chemical interaction of the N with the Ti sublattice [39,40]. The formation of Ti 2 AlC was also reported by plasma carburization of TiAl [41], although oxidation resistance of the carburized surface was apparently not studied.…”
Section: Ternary Nitride and Carbide Protective Surface Layer Formationmentioning
confidence: 90%
“…1.7) [38]. Inoue et al recently reported the plasma nitridation of TiAl to form Ti 2 AlN, and by quantum chemical simulation found evidence that formation of the ternary nitride was influenced primarily by chemical interaction of the N with the Ti sub-lattice [39,40]. The formation of Ti 2 AlC was also reported by plasma carburization of TiAl [41], although oxidation resistance of the carburized surface was apparently not studied.…”
Section: Ternary Nitride and Carbide Protective Surface Layer Formationmentioning
confidence: 91%